2021
DOI: 10.3389/fphar.2021.736951
|View full text |Cite
|
Sign up to set email alerts
|

Identification and Characterization of Key Differentially Expressed Genes Associated With Metronomic Dosing of Topotecan in Human Prostate Cancer

Abstract: Repetitive, low-dose (metronomic; METRO) drug administration of some anticancer agents can overcome drug resistance and increase drug efficacy in many cancers, but the mechanisms are not understood fully. Previously, we showed that METRO dosing of topotecan (TOPO) is more effective than conventional (CONV) dosing in aggressive human prostate cancer (PCa) cell lines and in mouse tumor xenograft models. To gain mechanistic insights into METRO-TOPO activity, in this study we determined the effect of METRO- and CO… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
16
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(16 citation statements)
references
References 67 publications
0
16
0
Order By: Relevance
“…Interestingly, metronomic Cyclophosphamide application also induced an immune reaction (in terms of T cell reactivation) in patients with biochemical recurrence ( 105 ). Although the mode of action of metronomic therapies is not completely understood, a recent study identified key genes which were associated with (metronomic) Topotecan dosing in PCa cell lines ( 106 ).…”
Section: Discussionmentioning
confidence: 99%
“…Interestingly, metronomic Cyclophosphamide application also induced an immune reaction (in terms of T cell reactivation) in patients with biochemical recurrence ( 105 ). Although the mode of action of metronomic therapies is not completely understood, a recent study identified key genes which were associated with (metronomic) Topotecan dosing in PCa cell lines ( 106 ).…”
Section: Discussionmentioning
confidence: 99%
“…Metronomic, very low-dose chemotherapy promotes a continuous pattern of stress responses [ 55 , 123 , 124 , 125 ]. The present clinical data reveal that metronomic chemotherapy at ‘very’ low-doses limits tumor tissue plasticity by stress response, probably decreasing phenotypic heterogeneity of tumor cell niches as tissue stress generally induces a tighter phenotype [ 123 , 126 , 127 , 128 , 129 , 130 , 131 ]. Thus, metronomic chemotherapy might induce phenotypic integration of inflammation control or differentiation by editing techniques and, consecutively, may serve as an enhancer of pro-anakoinotic effects mediated by added transcriptional modulators [ 55 , 123 ].…”
Section: Specific Therapeutic Access To M-crac With Tumor Tissue Edit...mentioning
confidence: 99%
“…METRO is an emerging treatment option that has shown promise for various cancer types, including prostate cancer ( 20–23 ). In our previous study, we reported that metronomic topotecan treatment (METRO-TOPO) was 2.4- to 18-fold more potent ( P < 0.05) compared with conventional topotecan (CONV-TOPO) treatment in prostate cancer cell lines ( 22 ). We then performed animal study with METRO-TOPO versus CONV-TOPO and demonstrated that by day 17, METRO-TOPO treatment resulted in significantly ( P ≤ 0.05) smaller tumor volume (65.4% ± 11.2%) compared with control (136% ± 14%) and CONV-TOPO–treated animals (138% ± 10%) in an aggressive xenograft tumor model of human prostate cancer implanted in male NCr athymic mice ( 22 ).…”
Section: Introductionmentioning
confidence: 99%
“…In our previous study, we reported that metronomic topotecan treatment (METRO-TOPO) was 2.4- to 18-fold more potent ( P < 0.05) compared with conventional topotecan (CONV-TOPO) treatment in prostate cancer cell lines ( 22 ). We then performed animal study with METRO-TOPO versus CONV-TOPO and demonstrated that by day 17, METRO-TOPO treatment resulted in significantly ( P ≤ 0.05) smaller tumor volume (65.4% ± 11.2%) compared with control (136% ± 14%) and CONV-TOPO–treated animals (138% ± 10%) in an aggressive xenograft tumor model of human prostate cancer implanted in male NCr athymic mice ( 22 ). This overall antitumor activity of METRO-TOPO was maintained through the end of the study, animals receiving METRO-TOPO dosing regimens had significantly ( P ≤ 0.05) smaller tumor volumes (54.8% ± 16.5%) than animals receiving CONV-TOPO dosing (144% ± 11%) or the control group (207% ± 26%; ref.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation